Strategi Pencegahan Penyalahgunaan Narkoba: Pembentukan Satgas Desa Cintaratu dan Edukasi Melalui Buku Saku - Ai Teti Wahyuni; Doni Ilyas; Syaripah Aliyah; Aidah Fitri Robi’ah Aziz; Anwar Fauzi (Ekspresi : Publikasi Kegiatan Pengabdian Indonesia, 2024)
This service program aims to increase public awareness of the dangers of drugs through the formation of a Task Force (SATGAS) and the launch of the book "Youth Anti-Drug Self-Resilience" as an effort to create a Drug-Free Village (BERSINAR). The method used is Participatory Action Research (PAR) involving observation and active participation of village communities in the socialization program. The results of this program show success in forming a SATGAS consisting of 17 members, as well as increasing public understanding, especially teenagers, regarding the dangers of drugs. The pocket book prepared by KKN students is also appreciated as a practical guide for the community. Collaborative strategies through education and community empowerment have succeeded in creating an environment that is more alert to drug abuse, with support from the West Java Provincial National Narcotics Agency (BNNP) which strengthens the effectiveness of the program.